The Relationship Between Utilization of Health Service Center (Posyandu) and the Nutritional Status of Infants during the Pandemic - El Farchia, Yuniar Nisa; Astuti, Dhesi Ari (The Indonesian Institute of Science and Technology Research, 2023)
The aim of this research is to investigate the relationship between the utilization of posyandu and the nutritional status of toddlers during the pandemic in Muneng Village, Candiroto Sub-district, Temanggung Regency, Central Java. The design of this research is cross-sectional. The sample taken is 59 toddlers using total sampling technique. The data were analyzed with a Chi Square test at 95% significance level . The results showed that 56 respondents (95%) utilized posyandu more than 3 times, and there were 3 respondents (27.8%) who utilized it less than 3 times. The nutritional status of the toddlers showed that most of the respondents had a good nutritional status, with 53 respondents (89.8%), while 6 respondents (10.2%) had a poor nutritional status. There was a relationship between the utilization of posyandu and the nutritional status of toddlers during the pandemic. The conclusion of this research is that posyandu activities are crucial in controlling the development of toddlers, especially in terms of their nutritional status. The recommendation is for mothers to be more active in utilizing posyandu activities.